Chloroplast genome of Tillandsia landbeckii Phil. (Bromeliaceae) a species adapted to the hyper-arid conditions of the Atacama and Peruvian desert - Chávez Galarza, Julio César (2021)
Tillandsia landbeckii Phil. is a vulnerable species belonging to the terrestrial Bromeliaceae family; it is highly adapted to extremely hyper-arid conditions of the Atacama Desert and Peruvian deserts. In this study, we sequenced, assembled, and annotated its chloroplast genome. T. landbeckii chloroplast genome is 159,131 bp in length, containing a large single-copy region of 87,164 bp, a small single-copy region of 18,521 bp, and a pair of inverted repeat regions of 26,723 bp. The GC content of the chloroplast genome is 37.33%. It encodes a total of 132 genes, including 86 protein-coding genes, 38 tRNA genes and 8 rRNA genes. The phylogenetic tree indicates that T. landbeckii is placed within the Bromeliaceae family and has a close relationship with T. marconae with 100% support.